Differential regulation of proopiomelanocortin (POMC) mRNA expression in hypothalamus and anterior pituitary following repeated cyanamide with ethanol administration - Kinoshita Hiroshi; Hishida Shigeru; Ameno Kiyoshi; Ijiri Iwao; Harbuz Michael S. (Vojnosanitetski Pregled)
Background/Aim. We have investigated proopiomelanocortin (POMC) mRNA expression in the arcuate nucleus of the hypothalamus (ARC) and the anterior lobe of the pituitary (AL) following repeated cyanamide-ethanol reaction (CER). Methods. Adult male Sprague -Dawley rats (250 −290 gr) were housed in a temperature and humidity controlled environment with free access to food and water. Four experimental groups were used as follows: saline (as control), cyanamide alone, ethanol alone and ethanol with cyanamide. The animals received daily intraperitoneal injections (i.p.) of cyanamide (10mg/kg, 60 min before ethanol dosing) with or without ethanol (1g/kg) for 5 consecutive days, and were sacrificed 60 min after the last dosing of ethanol. The results were presented as the mean ± SEM for each group. All groups within each data set were compared by one-way ANOVA followed by Fisher PLSD test for multiple comparisons. A value of p<0.05 was considered significant. Results. The POMC mRNA levels in ARC were significantly decreased with cyanamide compared to the control and ethanol alone (p<0.05 and p<0.05 respectively), but increased in AL following repeated CER. Conclusion. We speculate that this differential regulation of POMC mRNA expression may be partially involved in the preventive effects on alcohol intake in response to CER.